2023
DOI: 10.1007/s00330-023-09957-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics analysis from magnetic resonance imaging in predicting the grade of nonfunctioning pancreatic neuroendocrine tumors: a multicenter study

Abstract: Objectives To explore the potential of radiomics features to predict the histologic grade of nonfunctioning pancreatic neuroendocrine tumor (NF-PNET) patients using non-contrast sequence based on MRI. Methods Two hundred twenty-eight patients with NF-PNETs undergoing MRI at 5 centers were retrospectively analyzed. Data from center 1 (n = 115) constituted the training cohort, and data from centers 2–5 (n = 113) constituted the testing cohort. Radiomics feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…After screening titles and abstracts, 85 potentially eligible articles were identified. After full-text review, six articles were excluded because of insufficient information; thus, 26 articles were included in this systematic review ( 21 , 22 , 26 49 ). Among them, six studies lacked information on positive and negative diagnosis values; therefore, only 20 articles were eligible for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening titles and abstracts, 85 potentially eligible articles were identified. After full-text review, six articles were excluded because of insufficient information; thus, 26 articles were included in this systematic review ( 21 , 22 , 26 49 ). Among them, six studies lacked information on positive and negative diagnosis values; therefore, only 20 articles were eligible for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical data such as age, gender, tumor size, tumor shape, tumor margin and CT stage are closely related to the pathogenic process of PNETs and therefore should not be ignored in diagnostic models ( 27 29 , 47 , 49 ).,Liang et al. ( 37 ) built a combined model which can improve the performance (0.856, [0.730–0.939] vs. 0.885 [0.765–0.957]).…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics is a promising field in NEN management, offering advanced imaging analysis for enhanced tumor characterization, prognostication, and treatment response assessment. The fusion model combining radiomics signatures and radiological characteristics showed good performance in predicting the grade of nonfunctioning pancreatic neuroendocrine tumors, with AUCs of 0.956 in the training set and 0.864 in the testing set in the paper of Zhu et al, 2024 [ 100 ]. Ye et al showed an interpretable radiomics-based random forest model that can effectively differentiate between G1 and G2/3 pancreatic NETs, demonstrating favorable interpretability [ 101 ].…”
Section: Future Frontiers In Radiomicsmentioning
confidence: 99%
“…These features are subsequently utilized to develop diverse tumor diagnosis and prediction models using various machine learning, deep learning, and other algorithmic approaches (10). Numerous studies have elucidated the utility of CT-based and MRI-based radiomics in diagnosing and predicting PNET, showcasing its efficacy (11,12). However, MRI is contraindicated for certain populations, including individuals with claustrophobia or metal implants.…”
Section: Introductionmentioning
confidence: 99%